I'm having problem with calculating the functional derivative of $F$ with respect to $\phi(x)$ while

$$F = \int d^{4}x \phi^2 \partial_{\mu}\phi\partial^{\mu}\phi.$$

I want to obtain $\frac{\delta F}{\delta \phi}$ by making form of $$\delta F = \int d^{4}x \frac{\delta F}{\delta \phi}\delta \phi.$$

But, I am confused how could I compute $\delta F$ because of $\partial_{\mu}\phi$.


Beginning with $$ F[\phi] = \int d^{4}x \ \phi^2 \ \partial_{\mu}\phi \ \partial^{\mu}\phi $$

we replace $\phi$ with $\phi+\lambda\eta$: $$ F[\phi+\lambda\eta] = \int d^{4}x \ (\phi+\lambda\eta)^2 \ \partial_{\mu}(\phi+\lambda\eta) \ \partial^{\mu}(\phi+\lambda\eta) $$

Then we take the derivative w.r.t. $\lambda$ at $\lambda=0,$ and use integration by parts to remove any derivatives of $\eta$: $$ \frac{d}{d\lambda} \left. F[\phi+\lambda\eta] \right|_{\lambda=0} = \int d^{4}x \ \left( 2\phi\eta \ \partial_{\mu}\phi\ \partial^{\mu}\phi + \phi^2 \ \partial_{\mu}\eta \ \partial^{\mu}\phi + \phi^2 \ \partial_{\mu}\phi \ \partial^{\mu}\eta \right) \\ = \int d^{4}x \ \left( 2\phi\eta \ \partial_{\mu}\phi\ \partial^{\mu}\phi - \partial_{\mu}(\phi^2\ \partial^{\mu}\phi) \eta - \partial^{\mu}(\phi^2\ \partial_{\mu}\phi) \eta \right) \\ = \int d^{4}x \ \left( 2\phi \ \partial_{\mu}\phi\ \partial^{\mu}\phi - \partial_{\mu}(\phi^2\ \partial^{\mu}\phi) - \partial^{\mu}(\phi^2\ \partial_{\mu}\phi) \right) \eta \\ $$

The $\eta$-independent factor in front of $\eta$ is now the functional derivative: $$ \frac{\delta F}{\delta\phi} = 2\phi \ \partial_{\mu}\phi\ \partial^{\mu}\phi - \partial_{\mu}(\phi^2\ \partial^{\mu}\phi) - \partial^{\mu}(\phi^2\ \partial_{\mu}\phi) \\ = 2\phi\ \partial_{\mu}\phi\ \partial^{\mu}\phi - (2\phi\ \partial_{\mu}\phi\ \partial^{\mu}\phi + \phi^2 \partial_{\mu}\partial^{\mu}\phi) - (2\phi\ \partial^{\mu}\phi\ \partial_{\mu}\phi + \phi^2\ \partial^{\mu}\partial_{\mu}\phi) \\ = -2\phi\ \partial^{\mu}\phi\ \partial_{\mu}\phi - \phi^2\ \partial^{\mu}\partial_{\mu}\phi $$

  • $\begingroup$ Thank you. I solved it. You gave me a key : integration by parts :) $\endgroup$ – Seal Jan 19 at 15:11

HINT: When you're doing this variation, you're implicitly replacing $\phi \to \phi + \delta \phi$ and keeping all the terms linear in $\delta \phi$. So you have $$ \delta F = \int d^4x \left[ (2 \phi \, \delta \phi) \partial_\mu \phi \partial^\mu \phi + \phi^2 (\partial_\mu \delta \phi) (\partial^\mu \phi) \right]. $$ The first term is of the form $(\text{something}) \times \delta \phi$, but the second one isn't. So you need to get rid of the derivative on the $\delta \phi$ in the second term, somehow.

Do you know of any mathematical techniques where you can "shift" the derivative on one term in an integrand onto a different term in the integrand?

  • $\begingroup$ That is exactly what I want to know. Thanks, I solved. $\endgroup$ – Seal Jan 19 at 15:10

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.